Associations and prognostic significance of diffuse myocardial fibrosis by cardiovascular magnetic resonance in heart failure with preserved ejection fraction - Roy, Clotilde; Slimani, Alisson; de Meester, Christophe; Amzulescu, Mihaela; Pasquet, Agnes; Vancraeynest, David; Beauloye, Christophe; Vanoverschelde, Jean-Louis; Gerber, Bernhard L.; Pouleur, Anne-Catherine (Journal of cardiovascular magnetic resonance, 2018)
Background Increased myocardial fibrosis may play a key role in heart failure with preserved ejection fraction (HFpEF) pathophysiology. The study aim was to evaluate the presence, associations, and prognostic significance of diffuse fibrosis in HFpEF patients compared to age- and sex-matched controls. Methods We prospectively included 118 consecutive HFpEF patients. Diffuse myocardial fibrosis was estimated by extracellular volume (ECV) quantified by cardiovascular magnetic resonance with the modified Look-Locker inversion recovery sequence. We determined an ECV age- and sex-adjusted cutoff value (33%) in 26 controls. Results Mean ECV was significantly higher in HFpEF patients versus healthy controls (32.9 ± 4.8% vs 28.2 ± 2.4%, P <  0.001). Multivariate logistic regression showed that body mass index (BMI) (odds ratio (OR) =0.92 [0.86–0.98], P = 0.011), diabetes (OR = 2.62 [1.11–6.18], P = 0.028), and transmitral peak E wave velocity (OR = 1.02 [1.00–1.03], P = 0.022) were significantly associated with abnormal ECV value. During a median follow-up of 11 ± 6 months, the primary outcome (all-cause mortality or first heart failure hospitalization) occurred in 38 patients. In multivariate Cox regression analysis, diabetes (hazard ratio (HR) =1.98 [1.04; 3.76], P = 0.038) and hemoglobin level (HR = 0.81 [0.67; 0.98], P = 0.028) were significant predictors of composite outcome. The ECV ability to improve this model added significant prognostic information. We then developed a risk score including diabetes, hemoglobin and ECV > 33% demonstrating significant prediction of risk and validated this score in a validation cohort of 53 patients. Kaplan–Meier curves showed a significant difference according to tertiles of the probability score ( P <  0.001). Conclusion Among HFpEF patients, high ECV, likely reflecting abnormal diffuse myocardial fibrosis, was associated with a higher rate of all-cause death and first HF hospitalization in short term follow up. Trial registration Characterization of Heart Failure With Preserved Ejection Fraction. Trial registration number: NCT03197350 . Date of registration: 20/06/2017. This trial was retrospectively registered.